PENEGAKAN HUKUM BAGI PENGEMUDI KENDARAAN RODA DUA DIBAWAH UMUR TANPA SURAT IZIN MENGEMUDI DI WILAYAH HUKUM POLISI RESOR KOTA PEKANBARU BERDASARKAN UNDANG-UNDANG NOMOR 22 TAHUN 2009 TENTANG LALU LINTAS ANGKUTAN JALAN - Andi Arfan; Syaifullah Yophi A; Erdiansyah ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2014)
Some indication of the type of violations that exist , the perpetrators of school kids who drive a motor vehicle often occur in Pekanbaru , many teenage son who has not duly deserves to bring their own motor vehicles and ironically this problem plus the rider was not wearing a safety helmet . Logically , any violation of any kind has always been not seen by traffic police , this incident seems to have a common - ordinary course , any violation in doing school children / adolescents are more likely not safe alias problem when violations are done by children school / teen always looks traffic police officers . Law enforcement for drivers under the age of two-wheeled vehicle without a driver's license in the jurisdiction in Pekanbaru Police still have not been successful , as in the city of Pekanbaru there are still many children who brought the age of driving a two-wheeled motor vehicle that does not have a driver's license in the enforcement Barriers law for drivers under the age of two-wheeled vehicle without a driver's license is still weak oversight made by the parents , and the lack of legal knowledge of the parents , so the giving vehicles to young children , but it is also still a lack of knowledge and society pehamanan khususnyaa children children who are still under the age of traffic rules then efforts are being made to overcome the barriers in law enforcement for drivers under the age of two-wheeled vehicle without a driver's license , to socialize about traffic rules , ban for motorcyclists under age , and as a result the resulting feels need to be implemented .Keywords: Law Enforcement - Driver - Under Age - Driving License